The TRPA1 Channel in the Cardiovascular System: Promising Features and Challenges - Wang, Zhen; Ye, Di; Ye, Jing; Wang, Menglong; Liu, Jianfang; Jiang, Huimin; Xu, Yao; Zhang, Jishou; Chen, Jiangbin; Wan, Jun (Frontiers in Pharmacology, 2019)
Abstract: The transient receptor potential ankyrin 1 (TRPA1) channel is a calcium-permeable nonselective cation channel in the plasma membrane that belongs to the transient receptor potential (TRP) channel superfamily. Recent studies have suggested that the TRPA1 channel plays an essential role in the development and progression of several cardiovascular conditions, such as atherosclerosis, heart failure, myocardial ischemia-reperfusion injury (IRI), myocardial fibrosis, arrhythmia, vasodilation and hypertension. Activation of the TRPA1 channel has a protective effect against the development of atherosclerosis and myocardial IRI. Furthermore, TRPA1 channel activation elicits myocardium contractility and peripheral vasodilation. Moreover, activation of the TRPA1 channel induces a biphasic blood pressure response. However, loss of channel expression or blockade of its activation suppresses myocardial fibrosis and arrhythmia. In this paper, we review the recent progress of research on the TRPA1 channel and discuss its dual role in the cardiovascular system.